New iron chelators in anthracycline-induced cardiotoxicity - Kaiserová, Helena; Simunek, Tomás; Sterba, Martin; den Hartog, Gertjan J M; Schröterová, Ladislava; Popelová, Olga; Gersl, Vladimír; Kvasnicková, Eva; Bast, Aalt (Cardiovascular toxicology, 2007)
The use of anthracycline anticancer drugs is limited by a cumulative, dose-dependent cardiac toxicity. Iron chelation has long been considered as a promising strategy to limit this unfavorable side effect, either by restoring the disturbed cellular iron homeostasis or by removing redox-active iron, which may promote anthracycline-induced oxidative stress. Aroylhydrazone lipophilic iron chelators have shown promising results in the rabbit model of daunorubicin-induced cardiomyopathy as well as in cellular models. The lack of interference with the antiproliferative effects of the anthracyclines also favors their use in clinical settings. The dose, however, should be carefully titrated to prevent iron depletion, which apparently also applies for other strong iron chelators. We have shown that a mere ability of a compound to chelate iron is not the sole determinant of a good cardioprotector and the protective potential does not directly correlate with the ability of the chelators to prevent hydroxyl radical formation. These findings, however, do not weaken the role of iron in doxorubicin cardiotoxicity as such, they rather appeal for further investigations into the molecular mechanisms how anthracyclines interact with iron and how iron chelation may interfere with these processes.
Keywords: Cardiotonic Agents; železo; Heart Diseases; Oxidative Stress; antracykliny; Iron Chelating Agents; chelátory železa; kardiotonika; Anthracyclines; oxidační stres; Animals; Humans; Iron; lidé; zvířata; Antibiotics, Antineoplastic; nemoci srdce; protinádorová antibiotika